1986
DOI: 10.1152/jappl.1986.61.3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive and psychomotor tasks on breath-holding span

Abstract: Bartlett (J. Appl. Physiol. 42: 717-721, 1977) demonstrated that a psychomotor task (hand dynamometer) extended breath holds at functional residual capacity (FRC) in a manner comparable to Valsalva and Mueller maneuvers. This led us to the hypothesis that distraction of a subject's attention from dyspneic sensations accounted for Bartlett's findings. This hypothesis was tested by comparing a hand dynamometer task (rubber-bulb squeeze) with a mental performance task (mental arithmetic). Results for tasks perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…), and mental distractions (Alpher et al. ). As there is arguably considerable cognitive stress involved with breath holding, this also needs to be acknowledged within the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), and mental distractions (Alpher et al. ). As there is arguably considerable cognitive stress involved with breath holding, this also needs to be acknowledged within the current study.…”
Section: Discussionmentioning
confidence: 99%
“…) end‐inspiratory breath‐hold, (Alpher et al. ) prehyperventilation breath‐hold, and (Andersson and Schagatay ) prehyperoxia breath‐hold. A final repeated rebreathe breath‐hold protocol was performed to measure the peak sympathetic response during successive breath‐holds at increasing chemoreflex stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even within the same subject breath‐hold duration can be increased by 13–19% with distractions [either by motor tasks (Fig. 2) or by mental arithmetic (Alpher et al 1986)] or by 37% with successive trials (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the attention to the motor demands of the activity diverting attention from breathing itself might well serve to oset a component of the acuity of the sensation reported as dyspnoea (Douglas and Haldane 1909;Hill and Flack 1910). It has been reported, for example, that t BH can be prolonged in resting subjects if they are doing mental arithmetic (Alpher et al 1986) or squeezing a rubber ball (Bartlett 1977;Alpher et al 1986); interestingly, however, this was reported not to be the case during passive exercise (Craig and Babcock 1962). We believe that this attention-diverting effect of the dynamic exercise may subserve a similar role.…”
Section: Discussionmentioning
confidence: 99%